Effect of mindfulness on treatment motivation in patients with substance use disorder - Tanrıkulu, Ali Baran; Kayaoğlu, Kübra (Journal of Dependence, 2024)
Objective: This research aimed to assess the mindfulness levels among individuals with substance use disorder (SUD) and investigate its influence on treatment motivation. Method: A descriptive and cross-sectional study was carried out involving 184 SUD patients. Data collection utilized a Personal Information Form, The Mindful Attention Awareness Scale (MAAS), and the Treatment Motivation Questionnaire (TMQ). Results: A strong positive correlation was identified between MAAS and TMQ levels (r: 0.796, p<0.001). Furthermore, the mindfulness predictor variable was found to account for 63% of the variance in the treatment motivation predicted variable (R2: 0.632, p<0.001). The Beta coefficient of the predictor variable in the regression model was 0.795, indicating a significant positive impact of mindfulness on treatment motivation (p<0.001). Conclusion: The study revealed that the conscious awareness levels of participants were below average, suggesting that conscious awareness may be a suitable target for SUD treatment. Additionally, individuals with high mindfulness exhibited elevated treatment motivation, emphasizing the importance of incorporating mindfulness-enhancing practices in clinics for individuals with SUD.